Rethinking the Lord Chancellor's role in judicial appointments*. (2nd January 2017) - Gee, Graham
ABSTRACT: The judicial appointments regime in England and Wales is unbalanced. The pre-2005 appointments regime conferred excessive discretion on the Lord Chancellor, but the post-2005 regime has gone much too far in the opposite direction. Today, the Lord Chancellor is almost entirely excluded from the process of selecting lower level judges and enjoys only limited say over the selection of senior judges. In this article I argue that the current regime places too little weight on the sound reasons for involving the minister in individual selection decisions, including the scope for ministerial input to enhance judicial independence, to supply political leadership on judicial diversity and to render more effective the discharge of the Lord Chancellor's systemic responsibility for the justice system as a whole. I argue that shortlists reconcile the need to more fully involve the Lord Chancellor whilst at the same time ensuring that candidates satisfy a merit threshold.